Prognostic models for survival and consciousness in patients with primary brainstem hemorrhage - Zhou, Jingyi; Wang, Rui; Mao, Jizhong; Gu, Yichen; Shao, Anwen; Liu, Fengqiang; Zhang, Jianmin (Frontiers in Neurology, 2023)
Objectives: Primary brainstem hemorrhage (PBSH) is one of the most catastrophic spontaneous intracerebral hemorrhage diseases, with a mortality rate of 70-80%. We explored the predictive factors for survival and consciousness in patients with PBSH (ClinicalTrials.gov ID: NCT04910490). Methods: We retrospectively reviewed 211 patients with PBSH admitted to our institution between January 2014 and October 2020. Clinical outcomes included the 30-day survival rate and the 90-day consciousness rate as evaluated by the National Institutes of Health Stroke Scale score. Multiple logistic regression analysis was performed. Results: The overall 30-day survival rate of 211 patients with PBSH was 70%. Several predictive factors, including hematoma volume, hematoma location, activated partial thromboplastin time (APTT) upon admission, and therapeutic strategy, were significantly related to 30-day survival. Compared with conservative treatment, stereotactic aspiration in our prediction model is strongly associated with improved 30-day survival (odds ratio, 6.67; 95% confidence interval, 3.13-14.29; P < 0.001). The prognosis prediction model of 90-day consciousness, including factors such as mydriasis, APTT value, hematoma location, and hematoma volume upon admission, has a good predictive effect (AUC, 0.835; 95% confidence interval, 0.78-0.89; P < 0.001). Conclusion: In patients with PBSH, conscious state upon admission, coagulation function, hematoma volume, hematoma location, and therapeutic strategy were significantly associated with prognosis. Stereotactic aspiration could significantly reduce the 30-day mortality rate.